Occurrence of the heavy metals and PCBs in Accumulation Lake Modrac - Marjanović, Aleksandra; Đeđibegović, Jasmina; Omeragić, Elma; Šober, Miroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2021)
The accumulation Lake Modrac is a particularly important source of drinking water for inhabitants of the Tuzla region and few local settlements.The most significant point sources of organic contaminants in the accumulation Lake Modrac are waste water from households and industry. In this area, most of the settlements have neither sewage systems nor facilities for waste water treatment. Other potential point sources of pollutants are industrial plants. The most prominent are coal mines (Banovići and Đurđevik), metal and wood industry, plant for plastic production, and oil and oil derivatives warehouse.Few previously conducted surveys in the region showed the presence of the persistent organic pollutants and heavy metals in large extent. The objective of this study was to conduct a water quality survey targeting selected inorganic (Cd, Cr, Cu, Hg, Ni, Pb and As) and organic pollutants in the accumulation Lake Modrac in Bosnia and Herzegovina. The content of polychlorinated biphenyls (PCBs) determined with ELISA test, ranging from 3.23 to 6.19 µg/L (sum of 7PCBs).The most abundant metals (analyzed by graphite furnace AAS and mercury analyzer) at all five sampling locations were Pb (6.79-36.58 µg/L); Ni (5.81-10.43 µg/L) and Hg (1.08-6.10 µg/L).